An unusual case of spinal manifestations of sickle cell disease - Ratnaparkhi, Chetana; Chaukhande, Sushupti Milind; Dhok, Avinash; Barick, Devashis (Indian Journal of Case Reports, 2017)
Sickle cell disease (SCD) results from the presence of abnormal beta globin chains within hemoglobin. Overtime, the disease produces various spinal abnormalities as a result of chronic anemia which include marrow hyperplasia, reversion of yellow marrow to red marrow, and occasionally extramedullary hematopoiesis. Vaso-occlusion may manifest as ischemia and infarction whereas superimposed infection may lead to osteomyelitis. There is paucity of literature illustrating the spinal manifestations of the SCD in a single case. Hence, in the present work, we report the case of a 30-year-old male with SCD who presented with almost all the manifestations of the disease in the spine.